Synthesis and Characterization of Limonene-Based Sulfur Polymer - Orhan, Ramazan; Aydoğmuş, Ercan (Osman SAĞDIÇ, 2021)
In this research, a sulfur-based polymer has been synthesized with limonene extracted from orange peels. The synthesis process has been carried out by dropping limonene at 0 wt.%, 0.5 wt.%, 1 wt.%, 2 wt.%, and 4 wt.% ratios into the molten sulfur. The change in the chemical bond structure of the synthesized sulfur-based polymer is determined by Fourier Transform Infrared Spectrophotometer (FTIR). Moreover, the density, Shore D hardness, and thermal conductivity coefficient of the sulfur-based polymer are also characterized. According to the evaluations, it has been seen that limonene extracted from 1% orange peel gave the best results. It has been observed that the polymerization efficiency is low when used below 1 wt.% by mass. At higher rates, Shore D hardness of the sulfur-based polymer decreases, thus a softer polymer is obtained. Besides, the density of the sulfur-based polymer is approximately 2067 kg/m3, and the thermal conductivity coefficient is measured at an average of 0.25 W/m·K. As the content of limonene in the polymer mixture raises, the thermal conductivity coefficient decreases and a more porous structure is formed.

Bu araştırmada, portakal kabuklarından ekstrakte edilen limonen ile kükürt bazlı bir polimer sentezlenmiştir. Sentez işlemi, erimiş kükürt içerisine kütlece % 0, % 0.5, % 1, % 2 ve % 4 oranında limonen damlatılarak gerçekleştirilmiştir. Sentezlenen kükürt bazlı polimerin kimyasal bağ yapısındaki değişiklik Fourier Dönüşümü Kızılötesi Spektrofotometresi (FTIR) ile belirlenmiştir. Ayrıca, kükürt bazlı polimerin yoğunluğu, Shore D sertliği ve termal iletkenlik katsayısı da karakterize edilmiştir. Yapılan değerlendirmelere göre en iyi sonuçlar ağırlıkça % 1 portakal kabuğundan ekstrakte edilen limonen ile elde edilmiştir. Kütlece % 1'in altında limonen kullanıldığında polimerizasyon veriminin düşük olduğu gözlemlenmiştir. Daha yüksek oranlarda limonene kullanımı kükürt bazlı polimerin Shore D sertliği azaltmış ve böylece daha yumuşak bir polimer sentezlenmiştir. Ayrıca, kükürt bazlı polimerin ortalama yoğunluğu yaklaşık 2067 kg/m3 ve ısıl iletkenlik katsayısı da 0.25 W/m·K olarak ölçülmüştür. Polimer karışımındaki limonen içeriği arttıkça ısıl iletkenlik katsayısı düşmüş ve daha gözenekli bir yapı oluşmuştur.
Limonen Bazlı Kükürt Polimerinin Sentezi ve Karakterizasyonu
Keywords: Engineering; Mühendislik